The thirty-year genocide: Turkey's destruction of its Christian minorities, 1894-1924 - Morris, Benny (Harvard University Press, 2019)
A new understanding of the three waves of ethno-religious violence that swept Turkey from the last days of the Ottoman Empire to the early years of the Turkish Republic, arguing that all three were part of one purposeful genocidal program.--